Lichen planus-like keratosis: Another differential diagnosis for kaposi sarcoma - Marcela Clavellina-Miller; Gabriela Moreno-Coutiño; Sonia Toussaint-Caire; Gustavo Reyes-Terán (Wolters Kluwer Medknow Publications, 2015)
Epidemic Kaposi sarcoma is a common finding among HIV/AIDS patients that are not under antiretroviral treatment, and sometimes it is the first sign of the disease. However, it can be seen even in patients with undetectable viral load and high CD 4 cell count. Under these circumstances, the clinical presentation can be atypical in location or number. For this reason, the number of differential diagnosis is increased and biopsy of the suspicious lesions is essential for an accurate diagnosis and further apropiate treatment.